Functional neurological symptoms are a frequent and relevant comorbidity in patients with multiple sclerosis - Piliavska, Katya; Dantlgraber, Michael; Dettmers, Christian; Jöbges, Michael; Liepert, Joachim; Schmidt, Roger (Frontiers in Neurology, 2023)
Introduction Functional neurological symptoms (FNS) in multiple sclerosis (MS) have shown to be underinvestigated even though neurological diseases such as MS represent a risk factor for developing FNS. Comorbidity of FNS and MS can produce high personal and social costs since FNS patients have high healthcare utilization costs and a quality of life at least as impaired as in patients with disorders with underlying structural pathology. This study aims to assess comorbid FNS in patients with MS (pwMS) and investigate whether FNS in pwMS are associated with poorer health-related quality of life and work ability. Methods Newly admitted patients (234) with MS were studied during their stay at Kliniken Schmieder, a neurological rehabilitation clinic in Konstanz, Germany. The degree to which the overall clinical picture was explained by MS pathology was rated by neurologists and allied health practitioners on a five-point Likert scale. Additionally, neurologists rated each symptom reported by the patients. Health-related quality of life was assessed using a self-report questionnaire and work ability was assessed using the mean number of hours worked per day and information regarding disability pension as reported by patients. Results In 55.1% of cases, the clinical picture was completely explained by structural pathology due to MS. 17.1% of pwMS presented an overall clinical picture half or less of which could be explained by underlying structural pathology. PwMS with a higher comorbid FNS burden had a lower health-related quality of life and reported fewer working hours per day than pwMS with symptoms explained by structural pathology. Furthermore, pwMS with a full disability pension had a higher comorbid FNS burden than pwMS with no or partial disability pension. Discussion These results show that FNS should be addressed diagnostically and therapeutically since such symptoms are an important comorbidity in MS that is related to poorer health-related quality of life and lower work ability.